Evaluation Study on Impact of Non-Formal Education - Planning Commission (Planning Commission, 1988)
The non-formal education (NFE) scheme was introduced during the Sixth Plan in a few states as a Centrally Sponsored Scheme (CSS) to meet the educational needs of children who do not enroll themselves in formal schools because of poverty and illiteracy of parents and other socio-cultural factors. Though the scheme was originally conceived as a complementary mode of delivery of educational services for elementary school-age children, the number of NFE centers grew manifold over the years. Its phenomenal growth during the last two plan periods tends to suggest that NFE is being used as a major instrument to achieve UEE. Can NFE meet the educational needs of out of school children effectively ? Does it have the potential of being a major instrument to achieve UEE? All these are relevant issues in devising an appropriate strategy for achieving UEE in the country.
Programme Evaluation Organisation Planning Commission Government of India